THE RELATIONSHIP OF FAST FOOD AND FIBER INTAKE WITH CHOLESTEROL LEVELS IN THE 2021 BATCH OF NUTRITION PROGRAM STUDENTS TEUKU UMAR UNIVERSITY - Dira Rulia Partisa; Itza Mulyani; Teuku Muliadi; Nasrianti Syam (PT. Radja Intercontinental Publishing, 2025)
Cholesterol is a fat compound produced by the body and also found in animals. There are two types of cholesterol that play a role in various body functions, namely LDL (Low Density Lipoprotein) and HDL (High Density Lipoprotein). This study aims to determine the relationship between fast food and fiber intake and cholesterol in nutrition students class of 2021 at Teuku Umar University. This research uses quantitative methods with a cross sectional design. The sample selected was 52 people from 164 populations using simple random sampling technique. Data was collected by distributing food frequency questionnaires and 24 hour food recalls. Data analysis used the chi square test with a significance level of α= 0.05. Results: there was a relationship fast food consumption and cholesterol levels (p = 0.008), fiber intake did not relationship with cholesterol levels (p = 1.000). Conclusion: fast food consumption is related to cholesterol levels, and fiber intake and cholesterol levels are not related. It is recommended to reduce excessive intake of fast food and adopt a healthy and nutritious intake.